2018
DOI: 10.1101/242040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting the DNM3OS / miR-199a~214 cluster for the treatment of fibroproliferative diseases

Abstract: One Sentence Summary: The DNM3OS lncRNA is a reservoir of fibromiRs with major functions in fibroblast response to TGF-β and represents a valuable therapeutic target for refractory fibrotic diseases such as idiopathic pulmonary fibrosis (IPF).not peer-reviewed) is the author/funder. All rights reserved. No reuse allowed without permission.The copyright holder for this preprint (which was . http://dx.doi.org/10.1101/242040 doi: bioRxiv preprint first posted online Jan. 4, 2018; AbstractGiven the paucity of effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Genomic miRNA profiles have revealed several miRNAs that are known to affect fibroproliferation, epithelial-mesenchymal transition (EMT), and the TGF-β1 signaling pathway (28)(29)(30)(31)(32). Although studies of long noncoding RNAs in pulmonary fibrosis are limited, there appears to be an anti-fibrotic role for FENDRR (33) and a pro-fibrotic role for DNM3OS (34). In addition, studies in peripheral blood have identified biomarkers of disease (35) and disease outcome (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…Genomic miRNA profiles have revealed several miRNAs that are known to affect fibroproliferation, epithelial-mesenchymal transition (EMT), and the TGF-β1 signaling pathway (28)(29)(30)(31)(32). Although studies of long noncoding RNAs in pulmonary fibrosis are limited, there appears to be an anti-fibrotic role for FENDRR (33) and a pro-fibrotic role for DNM3OS (34). In addition, studies in peripheral blood have identified biomarkers of disease (35) and disease outcome (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA Airn alleviate liver fibrosis via the Kruppel-like factor 2 (KLF2)-endothelial nitric oxide synthase (eNOS)-soluble guanylate cyclase (sGC) pathway ( 18 ), while Zinc finger E-box binding homeobox 1 antisense 1 ( ZEB1-AS1 ) contributes to lung fibrosis by facilitating EMT ( 19 ). LncRNA DNM3OS is induced by TGF-β1 which results in the production of profibrotic microRNAs (miRNAs) ( 20 ), and targeting DNM3OS shows promising therapeutic effects in fibroproliferative diseases including IPF ( 21 ). As a critical regulator for IPF, the underlying molecular mechanism of DNM3OS in IPF pathogenesis remains elusive.…”
Section: Introductionmentioning
confidence: 99%